Analisis Strategi Pengembangan Usaha dan Pemasaran Produk Pada Usaha Narasa Potato - Lusi Ketrin Memah; Suryadi Samudra; Harnida Wahyuni Adda (Pusat Riset dan Inovasi Nasional, 2023)
The food and beverage business in Indonesia is a business that continues to grow. Seeing the increasing number of restaurants, cafes and other culinary attractions, this indicates that the food and beverage business is always eyed by all parties. The goal of Narasa Potato product development is to maximize product sales achievement and also to increase customer satisfaction with Narasa Potato products. At present there are also many businesses that have recently opened and then closed because they have not thought about the existing market competition. This study aims to analyze the business development strategy and product marketing at the